Perancang Sistem Informasi Administrasi Keuangan Desa Berbasis Web Di Desa Kalingara - Dormis Bili; Yulius Nahak Tetik; Mitra Permata Ayu (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
Kalingara Village still faces various obstacles in financial administration. Problems in general occur such as manual financial records, a long-time report making process, and data storage that is less organized and prone to loss or damage. This condition makes it difficult for village officials, especially the treasurer and village secretary, to search for data, prepare reports, and make decisions based on valid and up-to-date financial data. This research uses software engineering research methods with descriptive and qualitative approaches. This research is focused on the process of designing and developing a web-based information system for village financial administration, which aims to solve real problems in Kalingara village. The design of the Village financial administration information system in presenting information can be used as a reference in the development of the system by the next researcher and facilitate the creation of an information system for the processing of financial administration data in the village.